Putting the public first? An examination of the implications of the 2009 EAC report. Part two: Independent public schools - Fitzgerald, Scott; Rainnie, A. (UnionsWA, 2011)
Since at least the late 1990s, a significant body of research has established that ‘self-managing schools’ do not improve the quality of educational practices across the public education system or improve ‘student learning outcomes’ for all students. Indeed, it has been noted that on the contrary, for vast numbers of students, especially those who are already disadvantaged, this reform is coming to be seen as being extremely damaging. This outcome is clear in cases such as the Victorian, English and American education systems where self-managing schools have been most fully developed.